Estimation of physical composition in carcasses of holstein steers - Jardim, Pedro Osório da C.; Dode, Margot Alves Nunes; Osório, José Carlos da Silveira; Lüder, Werner Erwin (Pesquisa Agropecuaria Brasileira, 1991)
Carcasses of seventeen Holstein steers raised under feedlot conditions, from six to twenty-four months of age, were used. The objectives of this work were to evaluate the carcasses and to establish regression equations to estimate weight and percentages of muscle, bone and fat. Independent variables were: live weight, cold carcass weight, carcass length, leg length, Longissimus dorsi area, thickness of covering fat, and conformation. Dependent variables were: weight and percentages of bone, muscle and fat. It was observed that Holstein steers may be slaughtered as baby beef, producing lean meat. Weight of cool carcass was the main variable to estimate weights, while thickness of covering fat was the main measure to estimate percentages. Measurements of carcass length, leg length and conformation have shown to be of little value to evaluate physical composition of carcasses.